2014
DOI: 10.11604/pamj.2014.18.174.3449
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of p24 antigen among a cohort of HIV antibody negative blood donors in Sokoto, North Western Nigeria - the question of safety of blood transfusion in Nigeria

Abstract: IntroductionBlood transfusions remain a substantial source of HIV in SSA particularly among children and pregnant women. Aims and objectives: This aim of this retrospective study was to investigate the prevalence of p24 antigen among HIV antibody seronegative blood donors in Sokoto, North West Nigeria.MethodsA total of 15,061 HIV antibody negative blood donors with mean age and age range (29.2 ± 8.18 and 18-50 years) were screened for p24 antigen between January 2010 to July 2013 using the Diapro Diagnostic im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 27 publications
2
12
2
Order By: Relevance
“…The blood donor HIV rate of 1.3% in 2010 was also less than 4.1% of the general population [25]. These rates are within the estimated values ranging between 1.0 % and 6 % reported from other regions of the country for blood donors [4,5,[9][10]. Marked differences in the prevalence among regions in Nigeria is due to cultural differences, varying level of education, religion, differing socio-economic structure.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The blood donor HIV rate of 1.3% in 2010 was also less than 4.1% of the general population [25]. These rates are within the estimated values ranging between 1.0 % and 6 % reported from other regions of the country for blood donors [4,5,[9][10]. Marked differences in the prevalence among regions in Nigeria is due to cultural differences, varying level of education, religion, differing socio-economic structure.…”
Section: Discussionsupporting
confidence: 49%
“…Over the last decade many blood banks in the country have included screening for hepatitis C. The seroprevalence rate for HIV among blood donors is different in various parts of the country. It ranges from 1.0 to 5.8% [4,8,10]. A previous study showed fluctuating high seroprevalence rates among our blood donors 11 .…”
Section: Introductionmentioning
confidence: 75%
“…29 Unlike serology, NAT has the ability to detect occult HBV infection as well as preseroconversion "window" phase infections. 31,32 Cited costs of HIV, hepatitis B surface antigen, and HCV enzyme-linked immunosorbent assay are $5.7 $3.6, and $3.6/unit respectively; in contrast, corresponding RDTs cost $0.62, $0.50, and $0.40/unit. 33 The cited costs do not factor in the purchasing power parity; that is, $5.7 in Nigeria is the equivalent of $97.38 in the United States.…”
Section: Biological Testing and Pathogen Reduction Of Blood Productsmentioning
confidence: 99%
“…As earlier stated, CRF02_AG remains the predominant subtype among high risk groups in Oyo State. The strain is the predominant circulating virus in West Africa 6,20,27,42,43 . Although CRF02_AG was first described in Ibadan, Nigeria, the origin of the virus is still not known especially now that the strain is prevalent in several regions of the world.…”
Section: Subtypingmentioning
confidence: 99%
“…Diverse HIV-1 subtypes and recombinant forms (CRF02_AG, G, A, B, C, D, CRF06_cpx, URFs etc.) have been characterized in the country previously 6 . Several HIV-1 high risk groups such as commercial sex workers 7,8 , voluntary blood donors 9,10 , long distance drivers [11][12][13] , mammy markets contiguous to military facilities 14 etc.…”
Section: Introductionmentioning
confidence: 99%